Dansgaard‐Oeschger cycles: Interactions between ocean and sea ice intrinsic to the Nordic seas. (12th September 2013) - Dokken, Trond M.; Nisancioglu, Kerim H.; Li, Camille; Battisti, David S.; Kissel, Catherine
<x xml:space="preserve">Abstract</x> [1] Dansgaard‐Oeschger (D‐O) cycles are the most dramatic, frequent, and wide‐reaching abrupt climate changes in the geologic record. On Greenland, D‐O cycles are characterized by an abrupt warming of 10 ± 5°C from a cold stadial to a warm interstadial phase, followed by gradual cooling before a rapid return to stadial conditions. The mechanisms responsible for these millennial cycles are not fully understood but are widely thought to involve abrupt changes in Atlantic Meridional Overturning Circulation due to freshwater perturbations. Here we present a new, high‐resolution multiproxy marine sediment core monitoring changes in the warm Atlantic inflow to the Nordic seas as well as in local sea ice cover and influx of ice‐rafted debris. In contrast to previous studies, the freshwater input is found to be coincident with warm interstadials on Greenland and has a Fennoscandian rather than Laurentide source. Furthermore, the data suggest a different thermohaline structure for the Nordic seas during cold stadials in which relatively warm Atlantic water circulates beneath a fresh surface layer and the presence of sea ice is inferred from benthic oxygen isotopes. This implies a delicate balance between the warm subsurface Atlantic water and fresh surface layer, with the possibility of abrupt changes in sea ice cover, and suggests a novel mechanism for the abrupt D‐O events observed in Greenland ice cores.